1977
DOI: 10.1093/nar/4.9.3199
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the chromatin core particle in solution

Abstract: The shape and size of the nucleosomal core particle from chromatin has been examined by analysis of neutron and X-ray scattering data from dilute solutions. Calculations of scattering for many different models have been made and only one model was able to account for both the X-ray and neutron profiles. This model is an oblate structure with height about 5OX and diameter 110X. The DNA is mainly confined to two annuli located at the top and bottom respectively of the core particle positioned on the outside of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
42
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(51 citation statements)
references
References 36 publications
9
42
0
Order By: Relevance
“…The particle is described as a flat cylinder 110 A in diameter and 0 57 A in height. A similar shape and dimensions were found to be consistent 2,3 with the low angle neutron scattering from core particles in solution…”
Section: Introductionsupporting
confidence: 68%
“…The particle is described as a flat cylinder 110 A in diameter and 0 57 A in height. A similar shape and dimensions were found to be consistent 2,3 with the low angle neutron scattering from core particles in solution…”
Section: Introductionsupporting
confidence: 68%
“…SANS with contrast variation, especially when coupled with selective deuteration of individual components, can facilitate triangulation of the location of individual components within macromolecular complexes. For example, SANS with contrast variation was the first method to correctly predict the subunit organization of eukaryotic chromosomes (55), the structural orientation of protein and DNA within the nucleosome (56), and the organization of rhodopsin within retinal rod outer segment (57), as well as to triangulate the location of various proteins and RNA within the ribosome (58,59). Herein we use the combination of contrast variation SANS and selective deuteration of apoA1 to directly visualize the low resolution structure of the protein and lipid core components individually within biologically active reconstituted sHDL.…”
mentioning
confidence: 99%
“…We believe however, that the structures of both the histone octamer and the nucleosome need to be accurately determined. 5,6, and 7 in (1)], which incidently are neutron diffraction studies, as providing firm data against our structure. However, Braddock et al found that the pitch of the DNA superhelix in the nucleosome was 37A.…”
mentioning
confidence: 58%
“…All the same, Burlingame et al argue that their structure for the isolated histone octamer is more relevant to the structure of chromatin than that of the octamer within nucleosome core particles, and go on to propose a different model for the way in which DNA associates with the octamer to form a nucleosome. Their analysis has led to a hydrated spongelike structure and a shape for the octamer which disagrees with the results of x-ray solution scattering on both the octamer and nucleosome core particles (5)(6)(7), and which cannot be fitted into the lattice of nucleosome core crystals. These large discrepancies suggest that the structure proposed by Burlingame et (3).…”
mentioning
confidence: 77%